Improving EFL Students' TOEFL Listening Scores Through Signpost Words and Guided Note-Taking: A Pre-Test and Post-Test Experimental Study - Zetira Ahmad (Lembaga Penelitian Dan Pengabdian Masyarakat (LPPM) STAI Raudhatul Akmal, 2026)
The listening comprehension section of the Test of English as a Foreign Language (TOEFL) represents a formidable academic hurdle for English as a Foreign Language (EFL) learners, primarily due to the rapid, real-time processing of high-density academic vocabulary, natural speech rates, and highly complex, non-linear lecture structures. This study systematically investigates the pedagogical effectiveness of teaching explicit structural lecture cues—specifically